1982
DOI: 10.1007/bf02534586
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of tissue prostaglandin synthesizing capacity by increased ratios of dietary alpha‐linolenic acid to linoleic acid,

Abstract: Semipurified diets containing ratios of alpha-linolenic acid (18:3 omega 3) to linoleic acid (18:2 omega 6) of 1/32, 1/7, 1/1, and 3.5/1 in the form of corn oil, soybean oil, soybean/linseed oil mix and linseed oil were fed to rats for 2 months. The first 3 diets were fed to another group of rats for 4 months and to a group through the second generation. Fatty acid analysis of liver and spleen ethanolamine glycerophosphatide revealed that, as the level of 18:3 omega 3 in the diet increased, the elongated, desa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(31 citation statements)
references
References 15 publications
1
30
0
Order By: Relevance
“…Significant values are in bold. (Marshall and Johnston, 1982). Ratio ALA to LA (1:4) is much higher in walnuts than in the Western diet (1:20).…”
Section: Dietary Fatty Acids and Pcos S Kalgaonkar Et Almentioning
confidence: 98%
“…Significant values are in bold. (Marshall and Johnston, 1982). Ratio ALA to LA (1:4) is much higher in walnuts than in the Western diet (1:20).…”
Section: Dietary Fatty Acids and Pcos S Kalgaonkar Et Almentioning
confidence: 98%
“…Two recent studies investigating dietary ALA intake (53) and serum ALA levels (33) also found higher risk of colorectal cancer in women but lower risk in men. Although experimental data (18,19,25) have supported the protective effects of both shortchain and long-chain N-3 fatty acids, epidemiologic studies have found inconsistent associations for ALA versus DHA and/or EPA (21,33,53). The potentially inefficient metabolic conversion of nutritionally essential ALA to long-chain N-3's (54) coupled with the absence of ''healthier'' food sources rich in ALA, such as flax, on the FFQ may make it more difficult to evaluate the potential benefits of ALA.…”
Section: N-6 and N-3 Intake And Risk Of Colorectal Cancer Cancer Epidmentioning
confidence: 99%
“…Experimental studies report anti-inflammatory and anticarcinogenic effects in the colon for N-3 PUFAs [eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and a-linolenic acid (ALA)], highest in fish and seed oils, and adverse effects for N-6 PUFAs [linoleic acid (LA) and arachidonic acid (AA)] found in commercially popular oils and animal products (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Despite evidence supporting the N-6 to N-3 ratio as a biologically plausible target (9,14,16,(18)(19)(20), most epidemiologic studies have generally not found an association with colorectal cancer (21) and very few have been of prospective design (22,23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, eicosanoids produced from arachidonic acid are proinflammatory whereas those produced from n-3 fatty acids are anti-inflammatory (1,33). Because n-3 and n-6 fatty acids compete for both the enzymes that convert shorter-to longer-chain fatty acids (1,34) and the COX-2 enzyme (35)(36)(37), which converts the longer-chain fatty acids to precursors for eicosanoid synthesis, higher n-3 fatty acid intake may result in decreased production of proinflammatory eicosanoids that could play a role in the development of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%